Tinjauan Yuridis Pemberian Hak Atas Tanah di Wilayah Pesisir - Adhisty Radhita Vasya; Faustina Aida Irmadela (Jurnal Hukum Lex Generalis, 2025)
This study examines the legal aspects of land rights allocation in Indonesia's coastal areas, which are strategic zones rich in natural resources and have been utilized by local communities for generations. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that granting Land Rights (HAT) in coastal areas must comply with administrative requirements, including the Marine Spatial Use Conformity Permit (KKPRL). The case of Pagar Laut in Tangerang exemplifies legal deviations in land rights issuance without proper authorization, leading to environmental degradation and restricted public access. In response, the government has revoked procedurally and materially flawed certificates and enacted regulatory reforms following the Job Creation Law. The principle of land’s social function serves as a fundamental guideline to ensure that coastal land use delivers not only economic benefits but also promotes social justice and environmental preservation.